Did Wheat Breeding Simultaneously Alter Grain Concentrations of Macro- and Micro-Nutrient Over the Past 80 Years of Cultivar Releasing in China? - Hao, Baozhen; Ma, Jingli; Si, Luyao; Jiang, Lina; Wang, Xiaojie; Yao, Chong; Ma, Siyuan; Li, Chunxi; Gao, Zhiqiang; Wang, Zhimin (Frontiers in Plant Science, 2022)
Biofortification of wheat with mineral through crop breeding is a sustainable and cost-effective approach to address human mineral malnutrition. A better understanding of the trends of grain concentrations of mineral nutrients in wheat over the breeding period may help to assess the breeding progress to date. A 2-year field experiment using 138 Chinese wheat landraces and 154 cultivars was conducted. Grain concentrations of micronutrients (Cu and Mn) and macronutrients (N, P, and K) were measured and corrected for a yield level to elucidate the trends of these mineral nutrients over the 80 years of cultivar releasing and identify genetic variation for these mineral nutrients in cultivars and landraces. Large genetic variation exists for grain mineral nutrients concentrations among tested genotypes, indicating that selection for enhancing mineral nutrient concentrations in wheat is possible. Landraces showed a slightly wide genetic variation of grain Cu concentration and a much narrow variation of Mn concentration when compared to modern cultivars. Grain concentrations of Cu and Mn decreased slightly with increasing grain yield with a weak correlation, while N, P, and K concentrations declined obviously with increasing yield with a strong correlation, revealing that increased grain yield had a strong negative effect on grain concentration of macronutrients, but a relative weak negative effect on micronutrients concentrations. When considering the impact of the variation in yield on mineral concentrations, grain concentrations of Cu, Mn, N, P, and K in wheat cultivars released from 1933 to 2017 exhibited different trends with a year of variety release. Grain Cu, N, and P concentrations showed significant decreasing trends over a breeding period, while grain Mn and K concentrations showed no clear trend, suggesting wheat breeding in China over the past 80 years has decreased grain concentrations of Cu, N, and P, and did not alter Mn and K concentrations. Finally, a total of 14 outstanding accessions with high grain mineral nutrients concentrations/contents were identified, and these genotypes can be considered as promising donors for developing mineral-dense wheat cultivars.